2014
DOI: 10.1111/jop.12212
|View full text |Cite
|
Sign up to set email alerts
|

ANGPTL4 regulates the metastatic potential of oral squamous cell carcinoma

Abstract: Lymph node metastasis is a major factor for poor prognosis in oral squamous cell carcinoma (OSCC). However, the molecular mechanisms of lymph node metastasis are unclear. We determined that angiopoietin-like protein 4 (ANGPTL4) mRNA and protein expression were increased in OSCC cells established from the primary site in metastatic cases. In addition, ANGPTL4 expression in biopsy specimens was correlated with the presence of lymph node metastasis. Therefore, our initial findings suggest that OSCC cells expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 42 publications
4
23
0
Order By: Relevance
“…The role of ANGPTL4 involved in the regulation of angiogenesis remains controversial [ 15 , 22 , 23 ]. It has been demonstrated that ANGPTL4 could inhibit VEGF-induced cell proliferation, migration, and tubule formation in HUVECs and this effect was via the suppression of Raf/MEK/ERK signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of ANGPTL4 involved in the regulation of angiogenesis remains controversial [ 15 , 22 , 23 ]. It has been demonstrated that ANGPTL4 could inhibit VEGF-induced cell proliferation, migration, and tubule formation in HUVECs and this effect was via the suppression of Raf/MEK/ERK signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The role of ANGPTL4 in lipid metabolism has been well investigated [ 16 , 18 ], however, the role of ANGPTL4 in tumor biology remains largely undefined. Some reports suggested its tumor-suppressive function [ 19 , 20 ], but others claimed its oncogenic function [ 21 23 ]. The controversial results drive the need of further research to address the role of ANGPLT4 in tumor progression.…”
Section: Introductionmentioning
confidence: 99%
“…16 ANGPTL4 promotes oral squamous cell carcinoma metastasis by stimulating cell invasion. 17 ANGPTL4 induced by TGFβ via the Smad signalling pathway promotes breast cancer metastasis. 18 Recent reports indicate that the effect of ANGPTL4 on tumour metastasis may be mediated by integrin activation.…”
Section: Introductionmentioning
confidence: 99%
“…The 5-year survival rate is 90% for patients without metastasis, but <40% for patients with metastasis, suggesting that the regional lymph node metastasis (RLNM) is one of the most adverse prognostic factors (4)(5)(6)(7)(8)(9)(10). However, the mechanisms of metastasis are poorly understood (11). Therefore, molecular changes in a number of oncogenes and tumor suppressor genes associated with development of OSCC may be important clues for preventing this disease, and elucidating the molecular mechanisms involved in cancer metastasis is needed (3,4).…”
Section: Introductionmentioning
confidence: 99%